Identification of the Antithrombotic Mechanism of Leonurine in Adrenalin Hydrochloride-Induced Thrombosis in Zebrafish via Regulating Oxidative Stress and Coagulation Cascade - Li Liao (Frontiers Media S.A., 2021)
Thrombosis is a general pathological phenomenon during severe disturbances to homeostasis, which plays an essential role in cardiovascular and cerebrovascular diseases. Leonurine (LEO), isolated from Leonurus japonicus Houtt, showes a crucial role in anticoagulation and vasodilatation. However, the properties and therapeutic mechanisms of this effect have not yet been systematically elucidated. Therefore, the antithrombotic effect of LEO was investigated in this study. Hematoxylin-Eosin staining was used to detect the thrombosis of zebrafish tail. Fluorescence probe was used to detect the reactive oxygen species. The biochemical indexes related to oxidative stress (lactate dehydrogenase, malondialdehyde, superoxide dismutase and glutathione) and vasodilator factor (endothelin-1 and nitric oxide) were analyzed by specific commercial assay kits. Besides, we detected the expression of related genes (fga, fgb, fgg, pkcα, pkcβ, vwf, f2) and proteins (PI3K, phospho-PI3K, Akt, phospho-Akt, ERK, phospho-ERK FIB) related to the anticoagulation and fibrinolytic system by quantitative reverse transcription and western blot. Beyond that, metabolomic analyses were carried out to identify the expressions of metabolites associated with the anti-thrombosis mechanism of LEO. Our in vivo experimental results showed that LEO could improve the oxidative stress injury, abnormal platelet aggregation and coagulation dysfunction induced by adrenalin hydrochloride. Moreover, LEO restored the modulation of amino acids and inositol metabolites which are reported to alleviate the thrombus formation. Collectively, LEO attenuates adrenalin hydrochloride-induced thrombosis partly via modulating oxidative stress, coagulation cascade and platelet activation and amino acid and inositol metabolites.